"'Academic' is a dirty word": Intended impact pathways of an emerging academic health centre in tropical regional Australia. (12th October 2018) - Edelman, Alexandra; Taylor, Judy; Ovseiko, Pavel V.; Topp, Stephanie M.
Summary: Background: The Tropical Australian Academic Health Centre (TAAHC) is being established in northern Queensland across a vast rural geography. The study aim is to identify intended impact pathways and beneficiaries of TAAHC as well as experienced and anticipated challenges. Methodology: The study is an empirical case study nested within a comparative multi‐case study on academic health centres (AHCs). Data were collected from documents, observation, and interviews with 24 health system and university stakeholders. Intended impact pathways were identified abductively from analysis of aspirations and challenges. Results: Aspirations of TAAHC reflect an ultimate aim to improve the health of the northern Queensland population. Challenges were trust and communication, understanding value and return on investment, health system receptiveness to building a research culture, prioritising and influencing the research agenda, and structure of the health system. Discussion: The study identifies three interdependent transitions that comprise the main intended impact pathway in TAAHC. Stakeholders expected TAAHC to effect health systems change and improvement rather than drive discovery‐oriented academic research associated with AHCs elsewhere. Conclusion: The findings contribute to the empirical evidence base on the role of AHCs internationally and to ongoing initiatives to establish and resource AHCs in Australia.